Die Bedeutung des Rechners für eine problemorientierte Lehre – am Beispiel Oberstufengeometrie und Stochastik (mathematica didactica, 2004)
The central aim of our MadiN-modules is the development of contexts, helps, and interactive medias, which promote problem solving and mathematical modeling in order to give the possibilities to the future teacher to reflect his own problem solving, and to provide him with means to influence problem solving processes of his students. All modules were evaluated and optimized according to the results of this evaluation (formative evaluation). In this article we discuss two forms of problem oriented, internet based teaching materials: the free discovery of problems and the guided problem solving of a given mathematical problem. Our discussion is based on two modules, which were developed in Braunschweig, and their evaluation: (1) mathematics education concerning analytic geometry and applied linearalgebra, (2) statistics education.